Teddy is polite: caring & sharing - Krutop, Lee (Five Mile Pr Pty Ltd Australia, 2008)
This charming tale follows Teddy as he navigates social situations, demonstrating the importance of good manners. From saying "please" and "thank you" to listening attentively to friends, Teddy shows how politeness can brighten everyone's day. Through his actions, he teaches young readers the value of respect and kindness in their interactions.